Lizard in the clouds: a new highland genus and species of Gymnophthalmidae (Reptilia: Squamata) from Maringma tepui, western Guyana - Kok, Philippe J.r. (Zootaxa, 2009)
A new genus is erected for Pantepuisaurus rodriguesi gen. nov. sp. nov., collected at 2080 m elevation on Mount Maringma, a sandstone flat-topped table mountain (tepui) located in the eastern Pakaraima Mountains, at the GuyanaBrazil border. The new genus mainly differs from all other known gymnophthalmids by the following combination of characters: distinctive ear opening and moveable eyelids, limbs pentadactyl with all digits clawed, prefrontals present, interparietal and parietals forming a jagged, irregular posterior margin, three pairs of genials, second pair of genials in contact with only one infralabial, dorsal scales hexagonal, keeled, in transverse rows only, ventral scales imbricate, hexagonal, mucronate, broadly keeled, in transverse rows only, and hemipenis weakly bilobed with series of curved transverse plicae bearing mineralized spicules.